Distinct phenotypic features of neonatal murine macrophages. Issue 1 (17th November 2014) - Winterberg, Thomas; Vieten, Gertrud; Meier, Tatiana; Yu, Yi; Busse, Mandy; Hennig, Christian; Hansen, Gesine; Jacobs, Roland; Ure, Benno M.; Kuebler, Joachim F.
<x xml:space="preserve">Abstract</x> Neonates rely on their innate immune system. Resident tissue macrophages are considered to be initiators and regulators of the innate immune response and thus, appear to be especially important to neonates. We hypothesized that the phenotype and function of neonatal tissue macrophages differ from their adult counterparts. Peritoneal macrophages from neonatal (<24 h) and adult (6 weeks old) C57BL/6J mice were isolated and analyzed by high‐content chipcytometry. After stimulation for 6 h with LPS (0, 1, 10, 100 ng/mL), macrophage transcriptome was analyzed by microarray and cytokine release was measured using multiparametric bead assays. Antigen presenting capacity was compared by T‐cell stimulation assays. We observed that neonatal murine peritoneal macrophages are characterized by selective lack of expression of F4/80, MHC class II, and costimulatory molecules (CD80, CD86). Furthermore, we found differences in the transcriptome between neonatal and adult macrophages, unstimulated and after LPS stimulation. Although neonatal macrophages showed a significantly increased secretion of proinflammatory cytokines upon LPS stimulation, their potential to induce T‐cell proliferation was significantly reduced. In conclusion, we observed a distinct phenotype of the neonatal macrophage population. The specific functions of this macrophage population could help to understand the excessive inflammatory reactions observed in the very young.